Odpowiedzi

2010-04-14T20:31:50+02:00
2x - 3 = 3
2x=3+3
2x=6/:2
x=3

8x + 7 = 4x +3
8x-4x=-7+3
4x=-4/:4
x=-1
3(1 - x )= 0
3-3x=0
3x=0-3
3x=-3/:3
x=-1
2x-1 = 1
2x=1+1
2x=2/:2
x=1
3x + 2 = 2 x +4
3x-2x=-2+4
x=2
1 2 1
2010-04-14T20:32:30+02:00
2x-3=3
2x=3+3
2x=6/:2
x=3

8x+7=4x+3
8x-4x=3-7
4x=-4/:4
x=-1

3(1-x)=0
3-3x=0
-3x=-3/:(-3)
x=1

2x-1 = 1
2x=1+1
2x=2/:2
x=1

3x + 2 = 2 x +4
3x-2x=4-2
x=2
2 3 2
2010-04-14T20:34:22+02:00
2x-3=3
2x=3+3
2x=6 /2
x=3

8x+7=4x+3
-pffff.;p

3(1-x)=0
3-3x=0
3x=3-0
3x=3 /3
x=1

2x-1=1
2x=1+1
2x=2 /2
x=1
1 5 1